Financial Literacy and Digital Financial Literacy: The Mediating Role of Financial Planning and Control in Micro Furniture Enterprises - Aisyah Nur Aini; Muhammad Ali Fikri (Manunggal Halim Jaya, 2026)
The rapid digital transformation in the financial sector has prompted micro-entrepreneurs to adapt to increasingly complex financial environments. However, many micro-entrepreneurs, particularly in Indonesia’s furniture sector, still face significant challenges in financial management, a lack of structured planning systems, and limited digital financial literacy. These constraints hinder their ability to adopt digital financial services effectively and weaken their competitiveness in the digital economy. This study addresses the issue by examining the influence of financial literacy on digital financial literacy, with financial planning and control serving as a mediating variable. Using the theory of planned behavior as the theoretical foundation, the research explores how attitudes, perceived behavioral control, and intentions influence financial decision-making in a digital context. A quantitative approach was applied, involving 127 micro-enterpreneurs in the furniture industry as respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial literacy has a positive effect on both digital financial literacy and financial planning and control. Furthermore, financial planning and control positively mediate the relationship between financial literacy and digital financial literacy. These findings imply that improving financial literacy alone is not sufficient; it must be complemented with structured financial planning and control to strengthen digital financial competencies. Practically, this suggests that training programs and policy interventions should integrate financial education with digital adoption strategies to enhance the competitiveness and sustainability of micro furniture enterprises. Theoretically, the study contributes by extending the theory of planned behavior to explain financial behavior in the digital transformation era.